Challenging times for insurance, banking and financial supervision in Saudi Arabia (KSA) - Giuseppe Orlando; Edward Bace (Administrative Sciences, 2021)
The financial system in the Kingdom of Saudi Arabia (KSA) has a history of relative soundness, particularly in banking, due to comparatively strict and enforced domestic supervision, and supported by what has been for the most part a reasonably robust economy. However, the sector is facing challenges of a sluggish economy, need for reform and negative effects of the COVID-19 pandemic. This paper strives to assess how well the government thus far has responded to the challenges in the financial sector. The working hypothesis is that the insurance industry has improved its position, resulting in higher efficiency and profitability and lower risk. This is an industry historically plagued by too many players, financial issues and less than adequate controls. The analysis undertaken bears out the hypothesis, as revealed by the enhanced contribution made by the industry since the pandemic. Analysis suggests that strides have been made in that industry in terms of helping to diversify the economy with the onset of the pandemic. Moreover, evidence is provided that the sensitivity to changes in oil volumes (rather than to changes in oil prices) is a key risk factor for the financial sector in the KSA. These findings have implications for policy makers in terms of leveraging the pandemic conditions as an opportunity to drive further reform and diversify the economy with lower risk.
Keywords: 350; banking; COVID-19; insurance; regulation and supervision; Saudi Arabia